A method for contactless speed measurement of two-phase AC servomotors - Prempraneerach, Yothin; Pechpunsri, Wirog (My University, 1983)
A technique is presented for contactless angular speed measurement of two-phase AC servomotors. It is based on the measurement of the counter EMF of the motor, by balancing the voltage supplied to the motor by an amplifier against the counter EMF generated in the motor stator winding. The circuit is extremely simple, which minimizes cost, complexity and weight, and there is no requirement for mechanical coupling between motor and circuitry. The circuit can replace AC tachometers for speed measurement and for the provision of rate feedback in AC control systems. Circuit details and experimental results of the method are presented. © 1983 Taylor and Francis Group, LLC.